Comparing skill acquisition under varying onsets of differential reinforcement: A preliminary analysis. Issue 2 (26th July 2019) - Campanaro, Alexandra M.; Vladescu, Jason C.; Kodak, Tiffany; DeBar, Ruth M.; Nippes, Kasey C.
Abstract : The purpose of the current study was to evaluate the effect of implementing differential reinforcement at different times relative to the onset of teaching new skills to learners with autism spectrum disorder. Specifically, we first determined the most efficient differential reinforcement arrangement for each participant. Using the most efficient arrangement, we evaluated if differential reinforcement from the immediate onset, early onset, or late onset is the most efficient for learners to acquire a new skill. Three children diagnosed with autism spectrum disorder who have a history of receiving intervention based on the principles of applied behavior analysis participated in this study. The immediate onset of differential reinforcement resulted in the most efficient instruction in 6 of 7 comparisons. The results are discussed in light of previous studies and suggestions for future research are provided.